2007
DOI: 10.1242/jeb.011197
|View full text |Cite
|
Sign up to set email alerts
|

Automatic aeroelastic devices in the wings of a steppe eagleAquila nipalensis

Abstract: SUMMARY Here we analyse aeroelastic devices in the wings of a steppe eagle Aquila nipalensis during manoeuvres. Chaotic deflections of the upperwing coverts observed using video cameras carried by the bird (50 frames s–1) indicate trailing-edge separation but attached flow near the leading edge during flapping and gust response, and completely stalled flows upon landing. The underwing coverts deflect automatically along the leading edge at high angle of attack. We use high-speed digital video (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 27 publications
1
146
0
Order By: Relevance
“…A landing bird may thus generate greater time-averaged lift than drag during a pitch-up manoeuvre. This may help explain why the eagle observed by Carruthers et al (2007) would consistently approach its perch from below, and exhibited a rapid increase in altitude during its pitch-up phase. As the authors of that study suggested, this may be a means to aid deceleration by transferring kinetic energy to potential energy.…”
Section: Time-averaged Forcesmentioning
confidence: 91%
See 3 more Smart Citations
“…A landing bird may thus generate greater time-averaged lift than drag during a pitch-up manoeuvre. This may help explain why the eagle observed by Carruthers et al (2007) would consistently approach its perch from below, and exhibited a rapid increase in altitude during its pitch-up phase. As the authors of that study suggested, this may be a means to aid deceleration by transferring kinetic energy to potential energy.…”
Section: Time-averaged Forcesmentioning
confidence: 91%
“…But this would also increase the total added mass in time, making it difficult to stop the body late in the manoeuvre by producing a net thrust through −m aU . The sudden change in the direction of forces would tend to yield an uncontrolled perching manoeuvre, which is not observed (Green & Cheng 1998;Berg & Biewener 2010;Carruthers et al 2007). In the next two sections we extend the simple 1D force model equation (2.3) by discussing the effects of rotation on the added-mass force, and by modeling the circulation forces induced by vortex shedding.…”
Section: Added-mass Manipulation Through Frontal Area Changementioning
confidence: 99%
See 2 more Smart Citations
“…The examples include dangerous phenomena like §utter and bu¨eting of the wings and fuselage [4 6], vibrations in turbine engines [7] and helicopter blades [8], as well as applications in the design of bio-inspired air vehicles [9,10]. Furthermore, recent research on the growth of the lift force and drag reduction by active electromorphing [11] and aeroelastic boundary actuators [12,13] requires the analysis of FSI.…”
Section: Introductionmentioning
confidence: 99%